Unstoppable climate change? The influence of fatalistic beliefs about climate change on behavioural change and willingness to pay cross-nationally. (21st April 2019) - Mayer, Adam; Smith, E. Keith
ABSTRACT: Although climate change is an urgent problem, behavioural and policy responses have not yet been sufficient to either reduce the volume of greenhouse gas emissions or adapt to a disrupted climate system. Significant efforts have been made to raise public awareness of the dangers posed by climate change. One reason why these efforts might not be sufficient is rooted in people's need to feel efficacy to solve complex problems; the belief that climate change is unstoppable might thwart action even among the concerned. This paper tests for the effect of fatalistic beliefs on behavioural change and willingness to pay to address climate change using two cross-national surveys representing over 50, 000 people in 48 nations. Key policy insights The perception that climate change poses a risk or danger increases the likelihood of behavioural change and willingness to pay to address climate change. The belief that climate change is unstoppable reduces the behavioural and policy response to climate change and moderates risk perception. Communicators and policy leaders should carefully frame climate change as a difficult, yet solvable, problem to circumvent fatalistic beliefs.